2′-Fucosyllactose impacts the expression of mucus-related genes in goblet cells and maintains barrier function of gut epithelial cells. (October 2021) - Figueroa-Lozano, Susana; Akkerman, Renate; Beukema, Martin; van Leeuwen, Sander S.; Dijkhuizen, Lubbert; de Vos, Paul
Graphical abstract: Highlights: 2′-FL significantly induced TFF3 and CHST5 expression in human Goblet cells. Isolated HMOs, 2′-FL/lactose and pure 2′-FL protect T84 epithelial cell layers from A23187-induced barrier impairment. 2′-FL isolated from human milk, 2′-FL/Lac and pure 2′-FL exert different effects on Goblet cell gene expression. Abstract: Scope: Cost-effective microbial biosynthesis of 2′-fucosyllactose (2′-FL) allows its application in infant formula. The specific effects of 2′-FL on the gastrointestinal immune barrier are still largely unknown. Methods/results: Here, we quantified and compared the effects of HMOs isolated from human milk, 2′-FL/lactose (Lac), and 2′-FL on the expression of the mucus associated genes MUC2, TFF3, RETLB and the Golgi sulfotransferases, CHST5, and GAL3ST5, in human goblet cells. We also determined whether these compounds have protective effects on A23187-induced barrier disruption of human T84 gut epithelial cells in vitro . The impact of isolated HMOs and 2′-FL/Lac on the mRNA expression of the mucus-related genes was minor while pure 2′-FL significantly induced GAL3ST2 and CHST5 . Isolated HMOs, 2′-FL/Lac and 2′-FL all prevented A23187-induced barrier disruption in human T84 cells. Conclusion: Our findings indicate that 2′-FL modulates the secretory function of goblet cells and protects gut epithelial cells.